Is your prescription of distance running shoes evidence-based?. Issue 3 (18th April 2008) - Richards, C E; Magin, P J; Callister, R
Abstract : Objectives: To determine whether the current practice of prescribing distance running shoes featuring elevated cushioned heels and pronation control systems tailored to the individual's foot type is evidence-based. Data sources: MEDLINE (1950–May 2007), CINAHL (1982–May 2007), EMBASE (1980–May 2007), PsychInfo (1806–May 2007), Cochrane Database of Systematic Reviews (2 nd Quarter 2007), Cochrane Central Register of Controlled trials (2 nd Quarter 2007), SPORTSDiscus (1985–May 2007) and AMED (1985–May 2007). Review methods: English language articles were identified via keyword and medical subject headings (MeSH) searches of the above electronic databases. With these searches and the subsequent review process, controlled trials or systematic reviews were sought in which the study population included adult recreational or competitive distance runners, the exposure was distance running, the intervention evaluated was a running shoe with an elevated cushioned heel and pronation control systems individualised to the wearer's foot type, and the outcome measures included either running injury rates, distance running performance, osteoarthritis risk, physical activity levels, or overall health and wellbeing. The quality of these studies and their findings were then evaluated. Results: No original research that met the study criteria was identified either directly or via the findings of the six systematic reviews identified. Conclusion: The prescription of this shoe type to distance runners is not evidence-based.